Penerapan Media Papan Kebudayaan Sasambo Melalui Pendekatan CRT untuk Meningkatkan Hasil Belajar pada Mata Pelajaran Bahasa Indonesia Peserta Didik Kelas 2 SDN 45 Mataram - salahudin, m.salahudin; Amrullah; Maskur (Mataram University, 2025)
This study aims to improve the learning outcomes of second-grade students at SDN 45 Mataram by using the Sasambo Cultural Board media through the Culturally Responsive Teaching (CRT) approach. The type of research used is Classroom Action Research (CAR), employing the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The research instruments used were tests and documentation. Data were analyzed using written multiple-choice tests to assess students’ cognitive abilities in Indonesian language learning outcomes. The results of the study show an improvement in students’ learning outcomes as observed in cycle I and cycle II. In cycle I, 7 students achieved mastery while 8 students did not, resulting in a mastery percentage of 46% and non-mastery of 54%. In cycle II, there was a significant increase with 15 students achieving mastery and none remaining unmastered, reaching a 100% mastery rate. Thus, the use of the Sasambo Cultural Board media through the CRT approach effectively improved the Indonesian language learning outcomes of second-grade students at SDN 45 Mataram.